Properties of some monkey DNA sequences obtained by a procedure that enriches for DNA replication origins. - Zannis-Hadjopoulos, M (1985)
Twelve clones of monkey DNA obtained by a procedure that enriches 10(3)- to 10(4)-fold for nascent sequences activated early in S phase (G. Kaufmann, M. Zannis-Hadjopoulos, and R. G. Martin, Mol. Cell. Biol. 5:721-727, 1985) have been examined. Only 2 of the 12 ors sequences (origin-enriched sequences) are unique (ors1 and ors8). Three contain the highly reiterated Alu family (ors3, ors9, and ors11). One contains the highly reiterated alpha-satellite family (ors12), but none contain the Kpn family. Those remaining contain middle repetitive sequences. Two examples of the same middle repetitive sequence were found (ors2 and ors6). Three of the middle repetitive sequences (the ors2-ors6 pair, ors5, and ors10) are moderately dispersed; one (ors4) is highly dispersed. The last, ors7, has been mapped to the bona fide replication origin of the D loop of mitochondrial DNA. Of the nine ors sequences tested, half possess snapback (intrachain reannealing) properties.